Transition of E-Service Quality Dimensions from Diverse Business Settings to E-Learning : A Review from Learners’ Perspective - Singh, Navjit; Kaur, Kulvinder; Deol, Ramandeep S. (Indian Journal of Marketing, 2022)
The purpose of this article was to review the existing literature on dimensions of electronic service quality (E-SQ) with a focus on the e-learning context. The study aimed to establish the dimensions of e-learning service quality applicable to e-learning in developing countries from the learners’ perspective. The study compared and contrasted E-SQ dimensions in diverse business settings and provided a comprehensive view of important studies. An extensive literature review was conducted to find relevant papers on E-SQ and e-learning from various databases, including Scopus, Web of Science, and Google Scholar, with a time horizon ranging from 2005 – 2022. The study revealed immense variations in the nature and number of factors affecting E-SQ. However, ease of use, privacy & security, responsiveness, website design, and reliability are amongst the most cited ones. Additionally, a unique set of dimensions were discovered in this research to assess the online service quality of e-learning activities, namely quality course content, interactive interface, innovative technology features, and customer service support. The research implication is that it will help to evaluate online service quality in the virtual learning environment. This study will benefit academic researchers, application developers, educators, and policymakers.